FENOMENA PERJANJIAN PERKAWINAN SUKU DAYAK (ANALISA ADAT DAN KEADILAN GENDER DALAM ISLAM) - Imam Syafi'i; Mufidah CH; Suwandi Suwandi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The marriage agreement is a tradition or custom of the ancestral Dayak tribe in marriage which until now has been maintained and preserved. If one of the parties has behavior that can damage household harmony and violates the agreement, the agreed sanctions will be imposed. With this marriage agreement, it will become a buffer for domestic life, especially to act arbitrarily for men. The urgency of a tradition and how the context of this marriage agreement as gender justice in husband-wife relations is interesting to study. This study focuses on analyzing the customary marriage agreement of the Dayak tribe from the perspective of Asy-Syāțibi. Furthermore, this customary agreement is reviewed on the concept of gender justice through the Qirā’ah Mubādalah approach. The data collected is qualitative with the type of library research. Viewed from the perspective of ash-Syatibi customs, the customary marriage agreement is included in al-’Aw āid al-Jāriyah baina an-nās, namely the habits that apply in the community that gets legitimacy from the syāri’ as long as it is not out of the teachings of Islam, namely the creation of benefit. In terms of gender justice, marriage agreements can accommodate the equality of rights and obligations of husband and wife, especially women's rights which are often negated by the arbitrariness of men in controlling them. All actions that can make the household far from happiness, extinguish the feeling of love and affection can be avoided by the existence of an agreement.